Detection and control of Pseudomonas using phage and phage protein - Carvalhais, Jéssica Fernandes (Universidade Federal de Viçosa, 2019)
Bacteria from the genus Pseudomonas plays an important role in milk, meat and fish spoilage because it can produce thermo-tolerant lipolytic and proteolytic enzymes, which reduce both the quality and shelf life this product. Besides this, the colonization of these bacteria can in many cases facilitate the colonization of pathogenic bacteria and the formation of biofilms. Chapter 2 aims to develop a rapid technique based on affinity for the identification of Pseudomonas in liquid solutions and in biofilms by agglutination. For this, magnetic beads were affinity linked to a structural phage protein from the UFV-P2 phage, that is responsible for recognition and binding to structures in the bacterial cell membrane. This complex formed by the beads and the structural phage protein, when in contact with the bacteria Pseudomonas fluorescens and Pseudomonas aeruginosa tend to form agglutinates visible to the naked eye. The test developed was able to identify P. fluorescens and P. aeruginosa. The test developed was able to identify P. fluorescens and P. aeruginosa in solution after 30 s and 3 min respectively. The tests were negative for Pseudomonas putida. Lactococcus lactis, Listeria monocytogenes and Escherichia coli. The lowest detectable concentration of P. fluorescens in solutions was 10³ CFU-mL-¹ and 10⁴ CFU-mL-¹ for P. aeruginosa. The tests on biofilms of P. fluorescens the agglutination was observed in the first minute of contact and in the P. aeruginosa biofilms after 2 min. There was no difference in agglutination time in biofilms with 24 and 48 h of formation in both strains analyzed. Biofilms with 72 h showed slower agglutination, presenting a time of agglutination between 4 to 5 min. The agglutination test was negative in biofilms of E. coli. The tests with swab solution presented positive agglutination after 3 min of contact. The agglutination test was considered efficient for solutions containing P. fluorescens and P. aeruginosa also for identification in biofilms on stainless steel coupons. The agglutination test developed was classified as fast response and specific for P. fluorescens and P. aeruginosa. The development of technologies that allow the rapid detection of microorganisms is an important strategy for quality control in industries and safety of the population. Chapter 3 of this thesis describes the use of phage P10 to control and prevent biofilm formation. The objective of this study was to evaluate the effects of adding phage P10 during P. fluorescens biofilm formation. The effects of P10 on pre-formed biofilm on polystyrene plates after 6 h of contact and over the course of 48 h were also examined. In both cases the phage activity was evaluated under static and dynamic condition at room temperature. The titers of the bacteria and phage were 10⁵ CFU-mL-¹ and 10⁸ PFU.mL-¹, respectively. Phage P10 significantly reduced (p<0.05) the number of adhered cells during the biofilm formation and in pre-formed biofilm under static and dynamic condition. The phage activity was more effective in younger biofilms. Adding phages during the biofilm formation resulted in an average 2.5-log reduction in the number of adhered cells. When the phages were added to pre-formed biofilm at 12 h, there was a 1.2 log reduction in the number of adhered cells. The use of phage P10 for these purposes is becoming increasingly relevant in terms of pathogenic bacterial resistance to the sanitizers that are traditionally used in food industries. Using the P10 phage to control biofilm formation may be a promising alternative for use in the food industry. The use of phages or their proteins is an important tool for industries and studies that elucidate efficiency and applications in different areas are increasingly relevant. The results of this thesis show that the use of phage and phage proteins has positive results regarding its applicability in biotechnology.

As bactérias do gênero Pseudomonas desempenham um papel importante na deterioração do leite, carne e peixe, pois podem produzir enzimas lipolíticas e proteolíticas termotolerantes, que reduzem tanto a qualidade e o prazo de validade desses alimentos. Além disso, a colonização de outras bactérias pode, em muitos casos, favorecer a colonização de bactérias patogênicas e a formação de biofilmes. O capítulo 2 tem por objetivo desenvolver uma técnica rápida baseada em afinidade para identificação de Pseudomonas em soluções líquidas e em biofilmes por aglutinação. Para isso, beads magnéticos foram ligados por afinidade a uma proteína fágica estrutural do fago UFV-P2, que é responsável pelo reconhecimento e ligação a estruturas na membrana celular bacteriana. Este complexo formado pelos beads e pela proteína estrutural do fago, quando em contato com as bactérias Pseudomonas fluorescens e Pseudomonas aeruginosa, tendem a formar aglutinados visíveis a olho nu. O teste desenvolvido foi capaz de identificar P. fluorescens e P. aeruginosa em solução após 30s e 3min respectivamente. Os testes foram negativos para Pseudomonas putida. Lactococcus lactis, Listeria monocytogenes e Escherichia coli A menor concentração detectável de P. fluorescens em soluções foi de 10³ CFU-mL-¹ e 10⁴ CFU-mL-¹ para Pseudomonas aeruginosa. Os testes em biofilme de Pseudomonas fluorescens apresentaram aglutinação no primeiro minuto de contato e em biofilmes de P. aeruginosa após 2 min. Não houve diferença no tempo de aglutinação em biofilmes com 24 e 48 h de formação nas duas linhagens analisadas, porém biofilmes com 72 h apresentaram aglutinação mais lenta, apresentando um tempo de aglutinação entre 4 a 5 min. O teste de aglutinação foi negativo em biofilmes de E. coli. Os testes com solução de swab apresentaram aglutinação positiva depois de 3 min de contato. O teste de aglutinação desenvolvido foi considerado eficiente para soluções contendo P. fluorescens e P. aeruginosa e para identificação em biofilmes formados em cupons de aço inoxidável. O teste de aglutinação desenvolvido foi classificado como de resposta rápida e específico. O desenvolvimento de tecnologias que permitam a rápida detecção de microrganismos é uma importante estratégia para o controle de qualidade nas indústrias e para a segurança da população. O capítulo 3 desta tese descreve o uso do fago P10 com objetivo de controlar e prevenir a formação de biofilmes. O uso de fagos ou de suas proteínas é uma ferramenta importante para indústrias e estudos que elucidam a eficiência e as aplicações em diferentes áreas são cada vez mais relevantes. Os resultados desta tese mostram que o uso de proteínas fágicas e apresenta resultados positivos quanto à sua aplicabilidade em biotecnologia.
Detecção e controle de Pseudomonas utilizando bacteriófagos e proteínas fágicas
Keywords: Pseudomonas; Biofilmes; Controle biológico; Microbiologia de Alimentos